Екологічний норматив якості вод в Україні: необхідність і наслідки відсутності - Уберман, В. І.; Васьковець, Людмила Антонівна (Національний університет "Львівська політехніка", 2018)
The problem of approximation of Ukrainian water legislation to the EU environmental law is considered. The basic ecological and legal instruments for regulating the quality of surface waters are investigated. It is established that the modern Ukrainian paradigm of water protection policy requires radical changes that are concentrated around the notion of ecological normative of the quality of surface water bodies. It is proposed to recognize that the first steps of approximation, which were carried out in 2016–2017, cannot be judged as successful.
Keywords: забруднюючі речовини; екологічне законодавство; якість води; екологічна безпека; природокористування